DESIGN INTERACTIVE QUR’AN LEARNING FOR KINDERGARTEN BASED ON ANDROID - R Thabrani; Muh. Syahlan Natsir (Journal of Information Technology and Its Utilization, 2018)
The Institute for the Development and Development of Al Qur'an Kindergarten (LPPTKA) in Sidrap city is an organization of the Indonesian Youth Mosque Youth Communication Agency (BKPRMI). LPPTKA BKPRMI Sidrap city is an educational institution that seeks to foster and develop the reading, writing, understanding and practicing the Qur'an through TKA / TPA units. As is known, basic religious education for early childhood is very important, where basic religious education special attention to children. The Qur'an Education Park (TPA) has become a forum for debriefing the basics of religion for children such as learning iqro ', prayer, ablution and many more. The learning method used in most TPAs in Sidrap Regency still uses a general learning system such as using prayer books or iqra books so that students easily feel bored, especially when learning is very limited so that the knowledge gained is not maximal if they do not repeat home. By using an Android-based interactive learning application, it will provide a new way of learning and know technology to students so that it can increase the interest and quality of TK/TPA students in Sidrap district.